The Management and Prevention of Delirium in Elderly Patients Hospitalised in Intensive Care Units: A Systematic Review - Sarai Zaher-Sánchez; Pedro José Satústegui-Dordá; Enrique Ramón-Arbués; Jose Angel Santos-Sánchez; Juan José Aguilón-Leiva; Sofía Pérez-Calahorra; Raúl Juárez-Vela; Teresa Sufrate-Sorzano; Beatriz Angulo-Nalda; María Elena Garrote-Cámara; Iván Santolalla-Arnedo; Emmanuel Echániz-Serrano (Nursing Reports)
Background: Delirium or an acute confusional state (ACS) is characterised as being a frequent and complex hospital complication in older adult patients, which can affect their level of independence and increase patient morbidity and mortality. Critically ill patients in the intensive care unit (ICU) frequently develop ICU delirium, leading to longer hospital and ICU stays, increased mortality and long-term impairment. Objectives: This review aims to assess existing evidence of interventions that can be considered effective for the management and prevention of delirium in ICUs, reducing short-term morbidity and mortality, ICU and hospital admission times and the occurrence of other long-term complications. Methodology: For this systematic review, we searched Medline, PubMed, Cochrane Library, CINHAL, LILACS, SciELO and Dialnet from January 2018 to August 2024, in English, Spanish and French. MeSH descriptors were adjusted to search the different databases. We also checked Prospero for ongoing systematic reviews. Main results: The electronic search yielded a total of 2656 studies, of which 14 trials met the eligibility criteria, with a total of 14,711 participants. We included eight randomised clinical trial (RCTs), four cohort analyses, one systematic review and one observational trial, including participants over 65 years admitted to the ICU. Ten of these studies were based on pharmacological interventions, three of them examined non-pharmacological interventions and the remaining study examined mixed (pharmacological and non-pharmacological) interventions. Six placebo RCTs were included, plus four reported comparisons between different drugs. Regarding non-pharmacological interventions, nursing programmes focused on optimising modifiable risk factors or the use of therapies such as bright light are emerging. Regarding mixed interventions, we found the combination of invasive techniques and with sedoanalgesia. Conclusions: Due to its satisfactory level of sedation, dexmedetomidine is presented as a viable option because, although olanzapine offers safer results, postoperative administration angiotensin inhibitor systems significantly reduced the incidence of delirium. As for propofol, no significant differences were found. Among the non-pharmacological and mixed therapies, bright light therapy was able to reduce the incidence of delirium, and the combination of epidural/general anaesthesia was effective in all subtypes of delirium. Concerning the remaining interventions, the scientific evidence is still insufficient to provide a definitive recommendation.